Factors correlating with prolonged fatigue among emergency department nurses - Al-Abdallah, Ashraf M (J Res Nurs, 2019)
BACKGROUND: Fatigue affects nurses negatively and leads to physical, cognitive and emotional problems that may influence nurses' quality of life. However, there is a lack of studies about prolonged fatigue and its relationship with socio-demographic characteristics and job-related psychosocial factors among nurses, especially emergency nurses, worldwide and in Jordan. AIMS: This study aims to assess the relationship between demographic factors, physical health, psychological distress and job-related psychosocial factors (psychological job demands, job control and social support) and prolonged fatigue among emergency department nurses in Jordan. METHODS: A descriptive correlational study using a convenience sample was used to recruit 153 emergency nurses. Physical health Questionnaire, General Health Questionnaire, Job Content Questionnaire and Checklist Individual Strength were used. RESULTS: The majority of emergency nurses experienced abnormally prolonged fatigue, moderate health, high psychological distress, high job demands and low job control and social support. Significant negative relationships were addressed between job control, social support and prolonged fatigue, whereas income had a negative weak relationship. Psychological distress and job demands had a positive weak relationship with prolonged fatigue. There was a significant positive weak relationship between psychological distress, job demands and prolonged fatigue. Job-related psychosocial factors (with exception of social support) and mental health were the predictors of prolonged fatigue. CONCLUSIONS: Prolonged fatigue is a multidimensional phenomenon that can be affected by several factors such as job-related psychosocial factors and psychological health. These factors should be taken into consideration when testing and developing interventions to minimise prolonged fatigue among emergency nurses.